Éticas ambientais, sustentabilidade e direito do meio ambiente / Environmental ethics, sustainability and law - Pessoa, Flávia Moreira Guimarães (Revista do Programa de Pós-Graduação em Direito, 2015)
This article discusses the different proposals of environmental ethics and how they influence the construction of an environmental law. It states that the contemporary ethical debate focuses primarily on the intrinsic values as the foundation of moral and legal considerations, so that the content and extending the scope of protection of the fundamental right to the environment depend on the ethical-philosophical paradigm adopted, It is related to an anthropocentric ethic, a zoocêntrica ethic, a biocentric ethical or ecocentric ethics. It is worth mentioning that several international and national standards that deal with the right to the environment can not be automatically aligned to any of them, there is a wide scope for interpretation by the operator’s right, the very field of legal interpretation. Alongside this, we can see a frank evolution of legal norms toward new axiologies, away from the traditional anthropocentric view. The fundamental right of the environment causes a break in the current legal system, because all the legal doctrine is based on the subject of law, the man, while the standards of environmental law, national and international, increasingly, have recognized their rights of nature, regardless of the value it has for humans, in search of the man’s statement as an integral part of nature this way, the article points out the evolution of the conceptions of the fundamental right [human] the environment the right environment demonstrating not there is an antagonistic relationship between the latter and the fundamental right [human] the environment. What exists is a salute of respect, and the right environment the continent, the broadest. The right to the environment, would be nothing more then than a facet of environmental law, seen from the perspective of one of its integral parts, man.